Impact of Lifestyle-Oriented Motivation on Small Tourism Enterprises' Social Responsibility and Performance. (September 2019) - Wang, Caiping; Li, Gang; Xu, Honggang
Lifestyle-oriented motivation (LOM) is the reason that the owners of many small enterprises start and operate businesses in the tourism industry. Using a sample of guesthouses in historic Chinese towns, this study examines how LOM affects these small businesses' corporate social responsibility (CSR), performance, and owners' intentions to sustain operations. Applying the structural equation modeling approach to a sample of 154 guesthouses, this study finds that LOM positively influences CSR, performance, and owners' operational intentions. Specifically, LOM promotes each dimension of CSR activities (product, environment, community, employees, and heritage protection); however, it only increases firms' subjective performance and has no significant influence on their objective performance. The mediating effects of CSR and performance on the path from LOM to owners' operational intentions are also demonstrated. Lastly, the theoretical and managerial implications of the findings are discussed.